Coconut oil induced production of a surfactant‐compatible lipase from Aspergillus tamarii under submerged fermentation. (6th October 2016) - Das, Arijit; Bhattacharya, Sourav; Shivakumar, Srividya; Shakya, Sujina; Sogane, Swathi Shankar
Abstract : Filamentous fungi are efficient producers of lipases. The present study focuses on identification of a potent lipolytic fungus and enhancement of lipase production through optimization of nutritional and cultural conditions under submerged fermentation. Molecular characterization of the fungus by 18S rDNA sequencing revealed its identity as Aspergillus tamarii with 98% homology. Maximum lipase production was noted in mineral salts medium supplemented with coconut oil (2.5%, v/v). A combination of ammonium chloride (2%, w/v) and tryptone (2%, w/v) facilitated maximum lipase production at pH 5 of the production medium. A carbon: nitrogen ratio of 1:4 led to significant ( p < 0.00008) increase in the enzyme production in the presence of surfactant cetyltrimethylammonium bromide (0.5%, w/v). Maximum lipase activity (2, 32, 500 ± 192 U/ml/min) was recorded after 7 days of incubation at 25 °C on a rotary shaker at 120 rpm. A 9.8‐fold increase in lipase activity was recorded after optimization of the process parameters. Addition of crude lipase enhanced the oil stain removal activity of a commercially available detergent by 2.2‐fold. The current findings suggest the potentiality of this fungal lipase to be used in detergent formulation.